#TITLE_ALTERNATIVE# - WIRAWAN HADI (NIM 13203074), CAHAYA
Dynamic stability of electrical power system needs to be preserved so that system still operates if it given small disturbances. The efforts to improve dynamic stability can be helped by adding Power System Stabilizer (PSS) which placed on synchronous generator excitation system. The purpose of PSS placement is adding oscillation damping by the result of small disturbance like load increment. Dynamic stability analysis can be evaluated by eigen value analysis. Participation factor from each generator in rotor speed oscillation and rotor angle oscillation then used to decide where to locate PSS. This is become base of PSS placement on synchronous generator which have high participation to system instability. The result of simulation showed that PSS placement on synchronous generator which has high participation made power system reach steady state faster than power system without PSS placement.